Peningkatan Literasi Bencana Melalui Gerakan Literasi Sekolah Pada Siswa Sekolah Dasar Negeri Kaliwungu Kabupaten Kudus - Muhammad Navis Mirza (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Disasters that occur apart from natural factors are also caused by human activities. Almost all activities carried out by humans will have an impact on environmental damage and subsequently have an impact on disasters for humans themselves. Kudus Regency, in 2019 there were 28 flood events, 9 landslides and 167 fire incidents, although only 2 schools were affected. For this reason, early knowledge is needed, especially for students who are future agents who can reduce activities that can cause natural damage. The school literacy movement is expected to spur the formation of this mindset by inserting disaster literacy materials which include reading books, discussions and simulations. Community service for students at SD Negeri 1 Kaliwungu uses a method that is carried out by inserting disaster literacy materials in the school literacy movement program, as well as training students on emergency response. The main target is elementary school students in Kaliwungu District, Kudus Regency. The output of this community service is publication in scientific journals, students of SDN 1 Kaliwungu gain increased knowledge and skills in disaster so that they can be applied in everyday life.